ĐIỀU TRA NHIỄM VI RÚT VIÊM GAN B (HBV) Ở CỘNG ĐỒNG DÂN CƯ XÃ X (HUYỆN GIO LINH, TỈNH QUẢNG TRỊ) - О.В., Калинина; Phạm, Ngọc Quang; Võ, Viết Cường; Trần, Thị Nhài; Phạm, Thị Hà Giang (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE INVESTIGATION OF HEPATITIS B VIRUS INFECTION (HBV) IN X COMMUNE (GIO LINH - QUANG TRI PROVINCE) In the study blood collected from 260 residents in X commune (Gio Linh, Quang Tri) is examined for HBsAg by ELISA method and HBV-DNA by real - time PCR. It is found that HBsAg carrying rate is 11.15% (29/260), 13.04% for males and 10.12% for females (p > 0.05); 11.15% of the residents (29/260) are HBV-DNA positive, in which 15.22% for males and 8.93% for females. The rate of HBV-DNA positive in subjects with HBsAg (+) is 79.31% (23/29) and in subjects with HBsAg (-) is 2.60% (6/231);